Development and validation of a RP-HPLC method for simultaneous determination of five COVID-19 antiviral drugs in pharmaceutical formulations - Mohamed W. Nassar; Ahmed Serag; Mohamed A. Hasan; Mohamed Kamel (Scientific Reports)
Abstract A rapid, sensitive, and selective reversed-phase high-performance liquid chromatography (RP-HPLC) method was developed and validated for the simultaneous determination of five COVID-19 antiviral drugs: favipiravir, molnupiravir, nirmatrelvir, remdesivir, and ritonavir. The chromatographic separation was achieved on a Hypersil BDS C18 column (4.5 × 150 mm, 5 μm particle size) using an isocratic mobile phase consisting of water and methanol (30:70 v/v, pH 3.0 adjusted with 0.1% ortho-phosphoric acid) at a flow rate of 1 mL/min with UV detection at 230 nm. The optimized method demonstrated good chromatographic resolution with retention times of 1.23, 1.79, 2.47, 2.86, and 4.34 min for favipiravir, molnupiravir, nirmatrelvir, remdesivir, and ritonavir, respectively. The method was validated according to ICH guidelines, showing linearity in the concentration range of 10–50 µg/mL with correlation coefficients (r²) ≥ 0.9997 for all analytes. The limits of detection were 0.415–0.946 µg/mL, while the limits of quantification were 1.260–2.868 µg/mL. The method demonstrated high trueness (99.59-100.08%) and precision (RSD < 1.1%). The validated method was successfully applied to the determination of these drugs in their pharmaceutical formulations, with recovery values ranging from 99.98 to 100.7% and no significant interference from excipients. Comprehensive greenness and practicality evaluations using five assessment tools yielded favorable scores: AGREE (0.70), AGREEprep (0.59), MoGAPI (70%), BAGI (82.5), and CACI (79), indicating good environmental performance and excellent practical applicability for routine pharmaceutical quality control analysis. The multi-tool assessment confirmed the method’s environmental friendliness through strategic solvent selection and minimal sample preparation requirements, while demonstrating superior practical implementation characteristics including cost-effectiveness and accessibility in standard analytical laboratories.